Peningkatan quality of experience pada permainan online multiplayer berbasis Arduino dengan menggunakan MQTT server - Gabe Dimas Wicaksana; Maman Abdurohman; Aji Gautama Putrada (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2020)
Online multiplayer games require internet networks to play with opposing players more exciting because multiple players can fight each other. The game experiences lag, which is expressed as the quality of experience (QoE), is one of the most common problems for online multiplayer games, causing the games less exciting to play. This study examined the implementation of Message Queue Telemetry Transport (MQTT) as a communication protocol in multiplayer online games using Arduino and compared its performance against HTTP. QoE used data collected using the mean opinion score (MOS) method. The MQTT resulted in an average QoE score of 3.9 (Pingpong) and 4 (TicTacToe) MOS units, while on HTTP 3.8 (PingPong and TicTacToe). The use of the MQTT communication protocol can improve the QoE of multiplayer online game players compared to HTTP.